Learning Simulations in Increasing Satisfaction and Self-Confidence of Nursing Students - Trisnaningtyas, Wenny; Indriyawati, Nina; Suharto, Suharto; Metasari, Sherly; Mohd. Fadzil, Nurika Faizah (Poltekkes Kemenkes Semarang, 2024)
Background: Simulation activities are an effective teaching method to increase student participation. Assessing student satisfaction with simulation methods is also important because it has not been fully explored in previous research.Purpose: The purpose of this research was to analyze the relationship between simulation design scale, education practice questionnaire, students' self-confidence and self-confidence in learning for Bachelor of Applied Nursing students.Methods: This research was a cross sectional descriptive study conducted on Bachelor of Applied Nursing students at the Ministry of Health Semarang Health Polytechnic in June-September 2023. The sample used was a total sampling of 80 students who were in the third year of study. Data collection techniques were carried out using the Student Satisfaction and Self-Confidence in Learning Scale (SCLS), Simulation Design Scale (SDS), and Educational Practice Questionnaire (EPQ) questionnaires and then processed using the Spearman rank test to determine the relationship between the three.Results: The results of the Spearman rank test test show that SDS is strongly related to EPQ (0.744), SDS is strongly related to SSCL (0.681), while EPQ is very strongly related to SSCL (0.846) with a positive relationship between each variable. There is a significant relationship between the SDS, EPQ, SSCL variables in Bachelor of Applied Nursing students with a p-value <0.05.Conclusion: Nursing students' satisfaction and confidence with simulation-based learning correlated with students' confidence in clinical practice.